Effect of Ru substitution in tellurium bridged copper spin 12 system Ba2CuTeO6: Structure, magnetism and optical properties. (September 2021) - Pradhan, Suman Kalyan; Datta, Raktim; De, Subodh Kumar
Abstract: In this paper we have explored and analyzed the crystal structure, magnetic and optical properties of Ru doped double perovskite compound Ba2 CuTe1- x Ru x O6 ( x  = 0, 0.05 and 0.1). Detailed analysis of powder x-ray diffraction data at room temperature confirms the formation of single phase with monoclinic crystal structure (space group C 2 /m ). A careful deconvolution of Ru and Cu x-ray photoelectron spectra indicates the formation of mixed oxidation states: Ru (4+ and 5+) and Cu (2+ and 3+). Electron paramagnetic resonance (EPR) spectra also support the presence of EPR silent Cu 3+ ( S  = 0) ions. A broad overturn around 66 K in temperature dependent magnetization data of pure compound gets gradually suppressed in Ru doped samples. Magnetic frustration decreases with increase of Ru doping concentration due to different magnetic competitive interactions. Optical properties (change of color) are influenced due to the formation of 4 d (Ru) energy levels in the vicinity of Fermi level. Highlights: Ru doped Ba2 CuTeO6 crystalizes in monoclinic crystal structure (space group C 2 /m ). XPS spectra indicates the formation of mixed oxidation states: Ru (4+ and 5+) and Cu (2+ and 3+) in doped composition. Electron paramagnetic resonance (EPR) spectra support the existence of Cu 3+ . A broad overturn around 66 K in M-T data of pure compound gets gradually suppressed in Ru doped samples. Change of colour is influenced due to the formation of 4 d (Ru) energy levels in the vicinity of Fermi level.